2019
DOI: 10.3168/jds.2018-15135
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance profiles of 5 common bovine mastitis pathogens in large Chinese dairy herds

Abstract: The prevalence of antimicrobial resistance (AMR) is increasing in human and animal pathogens, becoming a concern worldwide. However, prevalence and characteristics of AMR of bovine mastitis pathogens in large Chinese dairy herds are still unclear. Therefore, our objective was to determine the AMR profile of bacteria isolated from clinical mastitis in large (>500 cows) Chinese dairy herds. A total of 541 isolates of the 5 most common species, Staphylococcus aureus (n = 103), non-aureus staphylococci (NAS; n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
80
8
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 42 publications
(42 reference statements)
14
80
8
3
Order By: Relevance
“…In addition, Streptococcus spp. was highly resistant to clindamycin (35.5%) and this percentage was slightly higher than in reports from China (28.7%) and Argentina (25.5%) [13,43]. Resistance to chloramphenicol was also found in all mastitis pathogens in this study (2.1-26.1%), as other studies in Korea have reported [38,44].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In addition, Streptococcus spp. was highly resistant to clindamycin (35.5%) and this percentage was slightly higher than in reports from China (28.7%) and Argentina (25.5%) [13,43]. Resistance to chloramphenicol was also found in all mastitis pathogens in this study (2.1-26.1%), as other studies in Korea have reported [38,44].…”
Section: Discussioncontrasting
confidence: 61%
“…Antimicrobial therapy is common in Korea, which is one of the key components for the control of infectious mastitis, so the emergence of the antimicrobial resistance in major mastitis pathogens such as methicillin-resistant S. aureus (MRSA) has been reported [12], and is a public health concern [13]. The dairy farm environment has also been reported as a reservoir for the distribution of antimicrobial resistance [14].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently isolated pathogens are Staphylococcus aureus, Escherichia coli, Klebsiella spp., Streptococcus spp., Mycoplasma spp., Enterobacter spp., Bacillus spp., and Corynebacterium species (Abebe et al, 2016;Gao et al, 2017;Hoque et al, 2018). Therefore, the accurate identification of pathogens that cause CM enables appropriate choices for antimicrobial treatment and preventive mastitis management (Preethirani et al, 2015;Van Boeckel et al, 2015;Cheng et al, 2019). Over the past two decades, a wide range of phenotyping and genotyping methods have been implemented to study mastitis-causing bacteria (Preethirani et al, 2015;Gao et al, 2017;Hoque et al, 2018;Cheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the accurate identification of pathogens that cause CM enables appropriate choices for antimicrobial treatment and preventive mastitis management (Preethirani et al, 2015;Van Boeckel et al, 2015;Cheng et al, 2019). Over the past two decades, a wide range of phenotyping and genotyping methods have been implemented to study mastitis-causing bacteria (Preethirani et al, 2015;Gao et al, 2017;Hoque et al, 2018;Cheng et al, 2019). Although culture-based techniques are traditionally used to detect CM bacteria, these methods are time-consuming and have the inherent drawback of not being applicable to non-cultivable bacteria (Baron et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the excessive use of antibiotics contributes to the development of antibiotic-resistant pathogens. In large Chinese dairy herds, the prevalence of antimicrobial resistance in mastitis pathogens is comparatively high [2]. Thus, exploring alternatives to antibiotics in mastitis therapy is urgently needed.…”
Section: Introductionmentioning
confidence: 99%